Learning English Through Communicative Language Teaching for Elementary School Students - Muttaqiin, Miftahul (Education and Social Sciences Review, 2023)
Communicative Language Teaching (CLT) method encompassed four methods: such as Communicative English Teaching, Practice Questions, Question and Answer Sessions, and Guessing Game. Additionally, the learning environment was designed to involve communicative activities, such as games, to avoid student’s boredom. This learning process offered students opportunities to enhance their language skills through communicative English teaching methods. This research was conducted at SDN Kolpajung Pamekasan, East Java. A qualitative descriptive approach was employed to examine the teaching and learning process via CLT to students in grade three to six. The results indicated that teachers should convey the right method in addressing student challenges and create enjoyable learning experiences. The students actively participated in the teaching and learning process. They seemed following teacher’s instructions cooperatively. Hence, learning occurs when the appropriate methods are applied, resulting in an engaging and running well of learning process. The present research contributes valuable experiences for researcher, enhancing his understanding and proficiency in teaching methodologies